JURIDICAL REVIEW OF LEGAL SANCTIONS FOR PEOPLE OF THE CRIME OF POLLING SUBSIDIZED GAS TO NOT SUBSIDIED FROM THE PERSPECTIVE OF ISLAMIC CRIMINAL LAW AND NATIONAL CRIMINAL LAW - Ricky Pratama Ginting; Sulaiman; Husnul Hayana Daulay (PT. Radja Intercontinental Publishing, 2023)
Legal protection is provided to the public or consumers, especially poor families who suffer losses in cases of mixing the contents of LPG cylinders by business actors. The position of poor families and the community is viewed from the Consumer Protection Law, users of subsidized 3 Kg LPG gas can demand legal protection if an accident occurs due to LPG mixing and are given administrative sanctions or criminal sanctions to business actors for their actions. The aim of this research is to find out how legal sanctions are against perpetrators of mixing subsidized gas into non-subsidized gas from the perspective of Islamic criminal law and national criminal law. This research uses a descriptive qualitative research method, with an empirical normative approach and uses a research approach, namely a library search approach. This approach is carried out by conducting research by looking for sources from various references such as theses, journals, theses and etc. The results of this research are that a person will be held responsible if they have committed a mistake that is prohibited by the rules or syara' and if they have fulfilled the elements of criminal responsibility, namely that a person has committed a prohibited act, the act was carried out of his or her own volition, and the perpetrator knows the consequences of the act. did it.